2021
DOI: 10.3389/fpsyt.2021.648367
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Psychological Interventions in Online and Face-to-Face Settings on DSM-5 and ICD-11 Maladaptive Trait Domains: An Exploratory Pilot Study

Abstract: While mental health treatments have proven to be effective for a range of mental health problems, there is comparably little research on its effects on personality disorders or difficulty (PD). New dimensional conceptualizations of PD such as the ICD-11 PD model enable the cost- and time-effective dimensional assessment of severity and style of PD. Furthermore, they constitute a promising tool to investigate PD, not only as a treatment endpoint but also as a predictive or influencing factor for mental health t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…Clinicians treating patients with depression and/or anxiety should routinely assess impairments in PF along with ACE as our study results imply that individuals with both PF impairments and reported ACE are more prone to severe and enduring symptomatology. Applied this way, pretreatment PF scores may inform the necessity and centrality of process‐based interactional experiences in the treatment of depression or anxiety disorders (Kerber et al, 2021) and could be used as a decision tool for “personalized medicine” (Bach & Simonsen, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians treating patients with depression and/or anxiety should routinely assess impairments in PF along with ACE as our study results imply that individuals with both PF impairments and reported ACE are more prone to severe and enduring symptomatology. Applied this way, pretreatment PF scores may inform the necessity and centrality of process‐based interactional experiences in the treatment of depression or anxiety disorders (Kerber et al, 2021) and could be used as a decision tool for “personalized medicine” (Bach & Simonsen, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The most predictive variables for trial discontinuation in the IG were younger age and higher personality dysfunction. In particular, the latter is a relevant predictor of the amount of guidance required in psychological interventions [92]. Tackling this issue may require, besides human-delivered guidance, adjusting app behavior and content according to dimensional measures of personality functioning or other dimensional conceptualizations of psychopathology such as HiTOP [20].…”
Section: User Engagement and Adverse Eventsmentioning
confidence: 99%
“…More research is needed to learn whether the dimensional constructs defining PDs may parallel specific functional domains ( [21], e.g., reward responsiveness and valuation, and their relationship with the disinhibition trait domain [22]). Such re-conceptualization of PDs may have an impact on treatment content [14], length [23], and format of delivery [24].…”
Section: Developing An Evidence Base To Make Differentiated Recommend...mentioning
confidence: 99%